Explaining the persistent effect of the Euro-Changeover on German restaurant prices - Eife, Thomas A. (Discussion paper series, 2011)
This paper studies the long-run effect of the 2002 changeover on restaurant prices in Germany. German restaurant prices increased significantly when the euro was introduced as a new currency but rather than returning to their re-changeover trend, restaurant prices appear to have stabilized on a higher path. This stands in contrast to the prediction of menu costs models or models of confusion-induced price increases as these models can only account for a transitory effect. The persistence of the increase suggests the existence of more than one price equilibrium. This multiplicity of price equilibria is a central part of the explanation proposed in the paper.
Keywords: Arbeitspapier; Graue Literatur